2022
DOI: 10.3390/agriculture12091414
|View full text |Cite
|
Sign up to set email alerts
|

VvMYBPA2 Regulated the Accumulation of Flavan-3-ols though Forming a Trimeric Complex in ‘Zaoheibao’ Grape

Abstract: Flavan-3-ols are monomers of Proanthocyanidins (PAs), which are important polyphenolic compounds in grapes. Previous studies had shown that VvMYBPA2 was closely related to grape flavan-3-ol monomers biosynthesis, but its regulatory network is still unclear. Here, we found that the contents of (+)-catechin and (−)-epicatechin, the enzyme activities of anthocyanidin reductase (ANR) and leucoanthocyanidin reductase (LAR) and the expression of VvANR and VvLAR1 were increased in the VvMYBPA2 overexpression grape le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…The pMD-VvMYBPA1 vector and pCAMBIA1300 empty vector conducted a double enzyme digestion using Hind III and Sal I, then connected two enzyme cleavage products using T4 DNA ligase (Supplementary Table S1), constructed 35S::VvMYBPA1 vector, and converted it into competent cells of Agrobacterium tumefaciens GV3101. Green grape leaves were infected with Agrobacterium tumefaciens containing empty and 35S::VvMYBPA1 vectors for 10 min, respectively [24]. After infection, put them into a light incubator for culture.…”
Section: Instantaneous Overexpression In Grape Leavesmentioning
confidence: 99%
See 1 more Smart Citation
“…The pMD-VvMYBPA1 vector and pCAMBIA1300 empty vector conducted a double enzyme digestion using Hind III and Sal I, then connected two enzyme cleavage products using T4 DNA ligase (Supplementary Table S1), constructed 35S::VvMYBPA1 vector, and converted it into competent cells of Agrobacterium tumefaciens GV3101. Green grape leaves were infected with Agrobacterium tumefaciens containing empty and 35S::VvMYBPA1 vectors for 10 min, respectively [24]. After infection, put them into a light incubator for culture.…”
Section: Instantaneous Overexpression In Grape Leavesmentioning
confidence: 99%
“…Previous studies had showed that UV-C irradiation positively regulated VvLAR enzyme activity to promote the accumulation of total flavane-3-ols in early grape fruits [23], but its molecular regulation mechanism was still unclear. At present, studies on the regulation of grape PAs accumulation by a MBW trimer complex have been reported [24,25]. In this study, the different period grape fruits after UV-C irradiation treatment were used as experimental materials to explore the molecule mechanism of flavane-3-ol monomers in grapes.…”
Section: Introductionmentioning
confidence: 99%